Privileged Biorenewable Secologanin‐Based Diversity‐Oriented Synthesis for Pseudo‐Natural Alkaloids: Uncovering Novel Neuroprotective and Antimalarial Frameworks. Issue 23 (28th October 2021) - Zhu, Huajian; Cai, Yunrui; Ma, Shijia; Futamura, Yushi; Li, Jinbiao; Zhong, Wen; Zhang, Xiangnan; Osada, Hiroyuki; Zou, Hongbin
Abstract: Bioprivileged molecules hold great promise for supplementing petrochemicals in sustainable organic synthesis of a diverse bioactive products library. Secologanin, a biorenewable monoterpenoid glucoside with unique structural elements, is the key precursor for thousands of natural monoterpenoid alkaloids. Inspired by its inherent highly congested functional groups, a secologanin‐based diversity‐oriented synthesis (DOS) strategy for novel pseudo‐natural alkaloids was developed. All the reactive units of secologanin were involved in these operation simplicity protocols under mild reaction conditions, including the one‐step enantioselective transformation of exocyclic C8, C8/C11, and C8/C9/C10 as well as the chemoenzymatic manipulation of endocyclic C2/C6 via the attack by various nucleophiles. A combinatory scenario of the aforementioned reactions further provided diverse polycyclic products with multiple chiral centers. Preliminary activity screening of these newly constructed molecules led to the discovery of antimalarial and highly potent neuroprotective skeletons. The application of green biorenewable secologanin in diversity‐oriented pseudo‐natural monoterpenoid alkaloid synthesis might encourage the pursuit of valuable bioactive frameworks. Abstract : Diversity win : The chameleon‐like behavior of secologanin in nature assures the sustainable, simple, efficient, and enantioselective diversity‐oriented synthesis of diverse bioactive non‐natural alkaloids.